A novel approach to the study of extensional flow-induced crystallization. (April 2021) - Amirdine, Juliana; Htira, Thouaïba; Lefevre, Nicolas; Fulchiron, René; Mathieu, Nathalie; Zinet, Matthieu; Sinturel, Christophe; Burghelea, Teodor; Boyard, Nicolas
Abstract: A systematic experimental investigation of the coupling between the extensional flow and the crystallization of a commercial grade polypropylene is presented. A modified Sentmanat extensional device allows one to generate a uniaxial extensional flow in the absence of gravity sagging and monitoring its effect on the kinetics of crystallization via in-situ visualization of the sample in polarised light. As compared to the shear induced crystallization, a three fold increase of the kinetics of the extension induced crystallization is found. The study is complemented by a post mortem analysis of the crystalline morphology by small angle X ray scattering ( S A X S ) and wide angle X ray scattering ( W A X S ). Highlights: Custom design of a commercial Sentmanat extensional fixture mounted in a rotational rheometer. Combination of measurements of the transient extensional viscosity with polarized light imaging. Comparison of quiescent, shear-induced and extension-induced crystallization. Post-mortem microstructure analysis by SAXS/WAXS on extended samples, according to Hencky strain rates.